2011
DOI: 10.1108/ssrp-01-2011-b0001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotion in Democratic Dialogue: A Self Study

Abstract: This study contributes to existing scholarship on democratic education by focusing explicitly on the affective dynamics of teaching with and for discussion. More specifically, the purpose of this research is to critically analyze the first author’s efforts to address the role of emotion in democratic dialogue within the context of classroom-based discussions and the work of preparing future social studies educators for their role as discussion facilitators. We found that despite the instructor’s stated goals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Reidel's and Salinas's (2011) previous self-study revealed that traditional conceptualizations of emotions as a private individualized experience and as something to be “controlled” predominate among teacher candidates. Based on these findings, Michelle made emotion a formal topic of study in the social studies methods course.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reidel's and Salinas's (2011) previous self-study revealed that traditional conceptualizations of emotions as a private individualized experience and as something to be “controlled” predominate among teacher candidates. Based on these findings, Michelle made emotion a formal topic of study in the social studies methods course.…”
Section: Resultsmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www. emerald.com/insight/1933-5415.htm In this reflective dialogue and self-study, we return to and build upon findings from previous research (Reidel and Salinas, 2011) bringing specific attention to the relationship between race and emotion. We recognize the intersectionality of our identities and how they inform our work as researchers and teachers.…”
Section: Feeling Race 237mentioning
confidence: 99%
“…However, the conception of politics as reasoned debate may be so ingrained in current models of civic preparation that attempts to spur critical awareness of emotion will meet with resistance from pre-service social studies teachers. Reidel and Salinas (2011) found it difficult to dislodge the theory of emotion as individual and private in a teacher education course that sought to engage emotions explicitly in classroom discussions of controversial issues. Despite the instructor's repeated efforts to bring attention to the role of emotions, students were critical of classmates they judged as being too “emotional” during class discussions.…”
Section: Literature Reviewmentioning
confidence: 99%